2022
DOI: 10.3390/fractalfract6110663
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Morphology, Fractal Dimensions, and Structure of (Titanium) Aluminosilicate Gel during Synthesis of Zeolites Y and Ti-Y

Abstract: Zeolite Y and Ti-containing zeolite Y (1%, 2% and 5% TiO2) were synthesized by a hydrothermal seed-assisted method. In order to evidence the evolution of morphology, structure, and fractal dimensions during the zeolitization process at certain time intervals, a small volume from the reaction medium was isolated and frozen by lyophilization. The obtained samples were characterized by scanning electron microscopy (SEM), wide-angle X-ray diffraction (XRD), and small-angle X-ray scattering (SAXS). The fractal dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This mixture was aged for 24 h at room temperature and further, 6 h at 100 °C in a Teflon-lined autoclave. The formation of the aluminosilicate gel and its evolution during the zeolitization process was described in detail in a study recently reported by our group [ 30 ]. In order to obtain the aluminosilicate support with suitable properties for photocatalysis, the treatment of the corresponding gel resulting from mixing sodium silicate with sodium aluminate was completed differently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixture was aged for 24 h at room temperature and further, 6 h at 100 °C in a Teflon-lined autoclave. The formation of the aluminosilicate gel and its evolution during the zeolitization process was described in detail in a study recently reported by our group [ 30 ]. In order to obtain the aluminosilicate support with suitable properties for photocatalysis, the treatment of the corresponding gel resulting from mixing sodium silicate with sodium aluminate was completed differently.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the effects of the experimental conditions during the processing of the synthesis gel on the structural and morphological properties of zeolite Y were evaluated. Previous studies showed the formation of zeolite Y crystalline phase during the sol–gel process [ 30 ]. Compared to the other porous supports used (MCM-48, KIT-6, SBA-15, hierarchical zeolite Y), microporous zeolite Y with the same concentration of TiO 2 (10%) seems to have a lower activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first studies on fractal objects [6], there have been many reports in the literature showing the fractal nature of surfaces [7]. Moreover, the link between fractal properties and their physical-chemical properties has often been depicted in the last years: the fractal properties of the catalysts [8][9][10][11], zeolites [12], electrodes in electrochemical applications [13][14][15][16][17][18][19], nanoparticles [20,21], dental surfaces [22] have been intensively studied. Understanding the impact of roughness on surface phenomena and, moreover, the fact that most surfaces are self-affine (self-similar and scaling with different amounts in different directions) opened a new chapter in the study of adsorption [10], catalysis [8][9][10][11], and electrochemical processes [14,15,[17][18][19]23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The first studies regarding the introduction of titanium into the zeolite Y framework by direct synthesis and the effect of Ti concentration on the zeolite structure were carried out by our group [20,21]. Zeolite Y is a faujasite molecular sieve with 7.35 Å diameter pores and a three-dimensional pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of the zeolitic network was obtained for 1 and 2% TiO 2 , and its partial disruption was observed for 5% TiO 2 . The synthesis of Ti-Y and the effect of titanium concentration on the formation of the zeolite Y structure were evaluated by freezing the sol-gel phases at various periods [21].…”
Section: Introductionmentioning
confidence: 99%